ANALYSIS OF THE EFFECTIVENESS OF THE BROKER CODE CLOSING POLICY IN RUNNING TRADE ON HERDING BEHAVIOR - Juwita, Ratna; Muryadi, Misye Berlianti; Ingriyani , Lini (I-iECONS e-proceedings, 2023)
The broker code closure policy in running trades carried out by the Indonesia Stock Exchange on December 6, 2021, aims to overcome herding behavior and make better price spreads in the Indonesian capital market. This study aims to determine the policy's success by examining the existence of herding behavior before and after the broker code closure policy is enforced using the Cross-Sectional Absolute Deviation method and by looking at price volatility during the research period. Based on the research that has been carried out, it is known that there is a herding behavior before the policy is implemented, and there is no herding behavior after the policy is enforced. This means that the broker code closure policy in running trades carried out by the Indonesia Stock Exchange has succeeded in overcoming the herding behavior contained in the Indonesian capital market but is still not effective in overcoming price spreads that occur in the Indonesian capital market because there is the market sentiment towards economic conditions that occur both nationally and globally.